Design, synthesis and biological evaluation of novel 3-phenylpropanamide derivatives with acyl hydrazone units - Liyun Yang (Elsevier, 2021)
In this study, a series of 3-phenylpropanamide derivatives with acyl hydrazone units were synthesized and characterized by 1H NMR, 13C NMR and HR MS. And the structure of compound III33 was confirmed by X-ray single crystal. The bioassay results showed that, compounds III8, III17, III22, and III34 showed excellent inhibition on Xanthomonas oryzae pv. pryzae (Xoo) with EC50 values of 7.1, 8.8, 9.5, and 4.7 μg/mL in vitro. The EC50 values of compounds III12, III14 and III33 against Ralstonia solanacearum (Rs) were 7.6, 7.6 and 7.9 μg/mL, respectively, all lower than the values of thiadiazol copper (TC) was 66.8 μg/mL and bismerthiazol (BT) was 72.4 μg/mL. Compounds III12, III14, III33, and III34 exhibited excellent antibacterial activity of more than 80% against Xanthomonas axonopodis pv. citri (Xac) in vitro. Besides, compounds III8 (51.4%) and III34 (52.1%) were highly effective against Xoo in vivo, outperforming TC (49.5%) and BT (47.8%). Compounds III8 (29.8%) and III34 (24.6%) were close to TC (41.7%) and BT (47.8%) in terms of protective efficacy against Xoo in vivo. Meanwhile, some of title compounds also displayed inhibitory effects against phytopathogenic fungi. In a word, this study illustrated that the structures combined with phenylpropane amide derivatives of the acyl hydrazone units could be used as potential antibacterial reagents in the future.